The Effect of Avocado to the Profile of Blood Urea Nitrogen (BUN) and Creatinine in Rats (Rattus norvegicus) Induced with Meloxicam - Anshar, Amelia Ramadhani; Bahar, Muhammad Akbar; Ikliptikawati, Dini Kurnia (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
Incidence of drug overdose during treatment of acute disease consequently leads to serious renal damage. As supporting treatment, administration of herbal medicine and food dietary are frequently developed. This research aimed to prove how the administration of avocado juice could lower the BUN and creatinine level in white rats induced with toxic doses of meloxicam. Meloxicam is a non-steroidal anti-inflamatory drug (NSAID), which is effectively used as an anti-inflamatory, analgesic, and antipyretic. Twenty four (24) male Wistar rats were assigned to 4 groups of six rats each (n=6). 1 ml of CMC 1% was administered to Control Group I, 30 mg/kgBB meloxicam and 1 ml of CMC 1% to Control Grup II, 30 mg/kgBB meloxicam and avocado juice 5 g/kgBB/day to Treatment Group I, and 30 mg/kgBB meloxicam and avocado juice 10 g/kgBB/day to Treatment Group II. The study was conducted over 8 days, then the level of Blood Urea Nitrogen and creatinine of the white rats were examined on the 1st and 8th day. The results were analyzed by Anova Two Way With Replication, then followed by T-test (α = 0,05) if there were difference. The Anova Two Way With Replication test showed that the mean of the four groups either the levels of Blood Urea Nitrogen or creatinine was significantly decreased (p<0,05). The decrease of BUN in the treatment group I was 27,17 27,17mg/dl and 17,83mg/dl while the decrease of creatinine level was 0,983mg/dl and 0,713mg/dl. The conclusion of this study was that avocado juice decreases level of Blood Urea Nitrogen and creatinine in white rats which exposed toxic doses of meloxicam.